Social capital and individual well-being in Poland: A voice in the discussion - Fałkowski, Jan; Łopaciuk-Gonczaryk, Beata (Journal of Public Governance, 2011)
In his recent paper, professor Czapiński analyzes the relationship between social capital and individual wellbeing in Poland. He concludes that the former has no impact on the latter, which is predominantly driven by human capital. In this paper, we show that this conclusion may not be warranted. Our discussion draws on both theoretical considerations and empirical analysis.